2005
DOI: 10.1021/ja0435135
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Anilido-Aldimine Zinc Complexes for Epoxide/CO2 Copolymerization

Abstract: Acyclic o-phenylene-bridged bis(anilido-aldimine) compounds, o-C(6)H(4){C(6)H(2)R(2)N=CH-C(6)H(4)-(H)N(C(6)H(3)R'(2))}(2) and related 30-membered macrocyclic compounds, o-C(6)H(4){C(6)H(2)R'(2)N=CH-C(6)H(4)-(H)N-C(6)H(2)R(2)}(2) (o-C(6)H(4)) are prepared. Successive additions of Me(2)Zn and SO(2) gas to the bis(anilido-aldimine) compounds afford quantitatively dinuclear mu-methylsulfinato zinc complexes, o-C(6)H(4){(C(6)H(2)R(2)N=CH-C(6)H(4)-N(C(6)H(3)R'(2))-kappa(2)-N,N)Zn(mu-OS(O)Me)}(2) (R = iPr and R' = iP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
137
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(146 citation statements)
references
References 72 publications
6
137
0
3
Order By: Relevance
“…For the CO 2 /epoxide copolymerization, tetradentate derivatives of this ligand have been developed to bind rare earth metals [23] as well as to form a rigid bimetallic zinc acetate complex. [24] As a new alternative to the classic b-diketimines, new aminoimidoacrylate (AIA) ligands and their zinc acetate complexes, which showed high activities in the CO 2 /cyclo-hexene oxide copolymerization, have been reported by our group. [25] In this paper we present new derivatives of this group of ligands, their catalytic behavior, some insight into the CO 2 /epoxide copolymerization and first results in the terpolymerization of CO 2 , cyclohexene oxide and lactide (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…For the CO 2 /epoxide copolymerization, tetradentate derivatives of this ligand have been developed to bind rare earth metals [23] as well as to form a rigid bimetallic zinc acetate complex. [24] As a new alternative to the classic b-diketimines, new aminoimidoacrylate (AIA) ligands and their zinc acetate complexes, which showed high activities in the CO 2 /cyclo-hexene oxide copolymerization, have been reported by our group. [25] In this paper we present new derivatives of this group of ligands, their catalytic behavior, some insight into the CO 2 /epoxide copolymerization and first results in the terpolymerization of CO 2 , cyclohexene oxide and lactide (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] In 2005 and 2006, Lee et al reported on anilido-aldimine ligands for the preparation of dinuclear zinc catalysts 5. [35,36] Due to the bimetallic nature of the complexes, activities were retained even under high dilution. Limberg, Hultzsch and co-workers as well as Harder and co-workers focussed on a BDI-like structure in their dinuclear catalysts 6 and 7.…”
mentioning
confidence: 99%
“…[34] So far,this complex represents the only homogeneous zinc catalyst for co-polymerization of propylene oxide and CO 2 .O ther homogeneous zinc-based systems for,f or example,c yclohexeneo xide/CO 2 co-polymerization have not been reported to be active for the synthesis of poly(propylene carbonate). [17,21,25,29,30] Previous catalyst research in our group was focused on heterogeneous zinc(II)glutarates for the co-polymerizationo fp ropylene oxide and CO 2 .I nt he course of these investigations, the experimental and theoretical results corroboratedt he necessity of two cooperating metal centers for any activity with heterogeneous zinc dicarboxylates. However,t he activities with such catalysts are restricted due to restrained surface area and diffusion limitations.…”
Section: Introductionmentioning
confidence: 92%
“…[19,21,[24][25][26][27][28][29][30][31] One major breakthrough was the synthesis of b-diketiminato (BDI) zinc complexes by Coates et al [19,32,33] Already minor steric and electronic variations in the ligand framework led to dramatic changes in catalytic behavior.I ntroducing electronwithdrawing groups enabled the formation of poly(propylene carbonate). [34] So far,this complex represents the only homogeneous zinc catalyst for co-polymerization of propylene oxide and CO 2 .O ther homogeneous zinc-based systems for,f or example,c yclohexeneo xide/CO 2 co-polymerization have not been reported to be active for the synthesis of poly(propylene carbonate).…”
Section: Introductionmentioning
confidence: 99%